Identification of amino acids inserted during suppression of UAA and UGA termination codons at the gag-pol junction of Moloney murine leukemia virus. - Feng, Y X (1990)
Expression of the murine leukemia virus pol gene occurs by translational readthrough of an in-frame UAG codon between the gag and pol coding regions. In a previous study, we mutated the UAG codon to UAA or UGA and demonstrated that both of these termination codons could be suppressed in reticulocyte lysates and in infected cells with the same efficiency as UAG. We now report the identity of the amino acids inserted in vitro in response to UAA and UGA in fusion products containing the gag-pol junction region. The results show that UAA, like UAG, directs the incorporation of glutamine, whereas UGA directs the incorporation of three amino acids, arginine, cysteine, and tryptophan. To our knowledge, this is the first report indicating misreading of UAA as glutamine and UGA as arginine and cysteine in higher eukaryotes. Interestingly, although our protein synthesis system presumably contains other known UAG and UGA suppressors, these tRNAs did not suppress the termination codons in our experiments. Thus, it seems possible that the sequence surrounding the gag-pol junction not only promotes suppression but also helps determine which tRNAs function in suppression.